“Sacrifice” Among Ahmadi Women - Winy Trianita (JURNAL INDO-ISLAMIKA, 2012)
In the world of religion, sacrifice is believed as a form of devotion toward the deities. Some theories suggest that every religion has its own system as well as function of sacrifice. Therefore, sacrifice cannot be perceived to have a singular meaning. This research focuses on the sacrifice practiced by the Ahmadiyah community, which is a controversial sect within Islam. By looking at the Ahmadi women in Indonesia, this study attempts to find out how women use sacrifice as an expression of agency. Instead of being victims or objects of sacrifice, women can, in fact, play a significant role in resisting discrimination against them by their male-dominated organization through sacrifice.